2020
DOI: 10.3390/cancers12041040
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Antitumor Efficacy of Heavily Vascularized Tumors by RAMBO Virus through Decreased Tumor Endothelial Cell Activation

Abstract: Vascularization is a common pathology for many solid tumors, and therefore anti-angiogenic strategies are being investigated as a therapeutic target for treatment. Numerous studies are also being conducted regarding the effects of oncolytic viruses, including Imlygic TM , an FDA approved oncolytic herpes simplex virus-1 (oHSV) for the treatment of highly vascularized tumors such as Kaposi sarcoma (NCT04065152), and brain tumors. To our knowledge, the effects of combining oncolytic HSV with angiogenesis inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Unfortunately, not all cancer cells within a tumor mass undergo active replication [ 103 ]. In addition, the TME contains non-tumoral cells such as immune infiltrates, fibroblast, and endothelial cells, which have been shown to not support the replication of OVs designed according to the aforementioned principles [ 104 , 105 ]. More recent approaches to restrict HSV-1 OVs to cancer cells include receptor retargeting [ 106 ], use of specific promoters to express critical viral genes [ 107 ], transcriptional and translational regulation of essential viral gene expression [ 108 ], and incorporation of miRNA target sites into viral genes [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, not all cancer cells within a tumor mass undergo active replication [ 103 ]. In addition, the TME contains non-tumoral cells such as immune infiltrates, fibroblast, and endothelial cells, which have been shown to not support the replication of OVs designed according to the aforementioned principles [ 104 , 105 ]. More recent approaches to restrict HSV-1 OVs to cancer cells include receptor retargeting [ 106 ], use of specific promoters to express critical viral genes [ 107 ], transcriptional and translational regulation of essential viral gene expression [ 108 ], and incorporation of miRNA target sites into viral genes [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male NSG mice (6–8 weeks old) were implanted with GBM12-RFP cells (2 × 10 5 cells) stereotactically into the right hemisphere (2 mm lateral and 2.5 mm posterior to bregma, 1 mm depth) as previously described ( Nair et al, 2020 ). Thirteen days after tumor implantation, craniectomy was performed over the tumor-implanted area.…”
Section: Methodsmentioning
confidence: 99%
“…This results in a significant extension of survival compared with bevacizumab monotherapy. The combination also increases oHSV infection and replication [103]. Another strategy demonstrated that chelating copper (Cu) could augment the efficacy of oHSV infection and replication by preventing angiogenesis and increasing the serum stability of oHSVs [104] (Figure 3).…”
Section: Anti-angiogenic Inhibitormentioning
confidence: 99%